Psychotic symptoms in heroin withdrawal: A case report - Surabhi Sharma,; Prerak Kumar,; Nitin Raut,; Shiv Prasad, (Indian Journal of Case Reports, 2021)
Opiate withdrawal-induced psychotic symptoms are not so common clinical finding in our practice. Here, we present the case of heroin withdrawal in a 25-year-old married male patient. The patient was hospitalized after exhibiting psychotic symptomatology (irritability, delusion of parasitosis, and auditory and visual hallucinations). This psychotic symptomatology was reported by the patient after he stopped heroin intake suddenly. Psychotic symptoms were in the fluctuating course and were not continuously present throughout the day, started approximately 12–14 h after the last intake. In this case report, we describe a rare case of opioid withdrawal-induced psychotic symptoms where the response was seen with antipsychotic risperidone.